Specific activation of CD4–CD8– double‐negative T cells by Trypanosoma cruzi‐derived glycolipids induces a proinflammatory profile associated with cardiomyopathy in Chagas patients. (3rd July 2017) - Passos, L. S. A.; Magalhães, L. M. D.; Soares, R. P.; Marques, A. F.; Nunes, M. do C. P.; Gollob, K. J.; Dutra, W. O.
Summary: Cardiomyopathy is the most severe outcome of Chagas disease, causing more than 12 000 deaths/year. Immune cells participate in cardiomyopathy development either by direct tissue destruction, or by driving inflammation. We have shown that CD4 – CD8 – [double‐negative (DN)] T cells are major sources of inflammatory and anti‐inflammatory cytokines, associated with the cardiac (CARD) and indeterminate (IND) forms of Chagas disease, respectively. Here, we sought to identify Trypanosoma cruzi ‐derived components that lead to activation of DN T cells in Chagas patients. Glycolipid (GCL), lipid (LIP) and protein‐enriched (PRO) fractions derived from trypomastigote forms of T. cruzi were utilized to stimulate cells from IND and CARD patients to determine DN T cell activation by evaluating CD69 and cytokine expression. We observed that GCL, but not LIP or PRO fractions, induced higher activation of DN T cells, especially T cell receptor (TCR)‐γδ DN T, from IND and CARD. GCL led to an increase in tumour necrosis factor (TNF) and interleukin (IL)‐10 expression by TCR‐γδ DN T cells from IND, while inducing IFN‐γ expression by TCR‐γδ DN T cells from CARD. This led to an increase in the ratio IFN‐γ/IL‐10 in TCR‐γδ DN T cells from CARD, favouring an inflammatory profile. These results identify GCL as the major T. cruzi component responsible for activation of DN T cells in chronic Chagas disease, associated predominantly with an inflammatory profile in CARD, but not IND. These findings may have implications for designing new strategies of control or prevention of Chagas disease cardiomyopathy by modulating the response to GCL. Abstract : This manuscript shows that the glycolipid‐enriched fraction from trypomastigotes of T. cruzi specifically stimulates CD4‐CD8‐ (double negative) T cells, inducing an inflammatory profile associated with Chagas disease cardiomiopathy.